The transverse strength of acrylic resin after Coleus amboinicus, Lour extract solution immersion - Devi Rianti (Dental Journal (Majalah Kedokteran Gigi), 2006)
A laboratoric experimental study was conducted on the transverse strength of acrylic resin after Coleus amboinicus, Lour extract solution immersion. The aim of this study is to know the difference of acrylic resin transverse strengths caused by immersion time variations in a concentrate solution. The study was carried out on unpolished acrylic resin plates with 65 × 10 × 2,5 mm dimension; solution with 15% Coleus amboinicus, Lour extract, and 30, 60, 90 days immersion times to measure the transverse strength and sterilized aquadest was used as control. Acrylic resin plates transverse strength was measured using Autograph AG-10 TE. The data was analyzed using One-Way Anova and LSD with 5% degree of significance. The result showed that longer immersion time will decrease the transverse strength of the acrylic resin plates. After 90 days immersion time, the transverse strength decrease is still above the recommended standard transverse strength.